Synthesis, Antibacterial and Antioxidant Evaluation of Novel 1-(5,7-Dichloro-1,3-benzoxazol-2-yl)-1H-pyrazolo[3,4-b]quinoline Derivatives - N. D. Jayanna; H. M. Vagdevi; J. C. Dharshan; T. R. Prashith Kekuda (Journal of Chemistry)
Some novel 1-(5,7-dichloro-1,3-benzoxazol-2-yl)-1H-pyrazolo[3,4-b]quinoline derivatives 8(a–f) were synthesized by reacting 5,7-dichloro-2-hydrazino-1,3-benzoxazole 4 and substituted-2-chloro-3-quinoline carbaldehydes using p-toluenesulfonic acid (PTSA) as a catalyst for the cyclisation. The target molecules have been characterized by IR, 1H NMR, 13C NMR, and mass spectral studies. The synthesized compounds were screened for biological activities, and some of the compounds have exhibited encouraging antibacterial and antioxidant activities. The compounds 8a and 8e showed potent antibacterial activity, whereas the compounds 8e and 8f act as antioxidants.